The Effect of Altitude Difference on Physical and Mechanical Properties of Scots Pine Wood Grown in Turkey - Sinop Province - Bulent Kaygin; Semih Esnaf; Deniz Aydemir (Drvna Industrija, 2017)
In this study, the effect of altitude difference on the physical and mechanical properties of Scots pine (Pinus sylvestris L.) wood was investigated. For this purpose, nine Scots pine trees were selected from three altitudes: 250 m (low altitude), 700 m (intermediate altitude), and 1200 m (high altitude) located in the forestry of Sinop province (Black Sea Region in Turkey). For the physical properties of wood: air and oven dry specific gravity were determined, and for the mechanical properties of wood: compression strength parallel to the grain, static bending strength and modulus of elasticity in static bending were determined. Moreover, the variation of all wood properties was determined related to the altitude difference. The results of statistical analyses showed that the altitude difference was an important factor influencing the physical and mechanical properties of Scots pine wood. The air and oven dry density, compression strength parallel to the grain, static bending strength and modulus of elasticity in static bending were higher at intermediate altitude than at other altitudes.